Without Bounds : The Life and Death of Rabbi Ya'aqov Wazana - Bilu, Yoram; Project Muse. (Detroit : Wayne State University Press, 2017)
Without Bounds illuminates the life of the mysterious Rabbi Ya'aqov Wazana, a Jewish healer who worked in the Western High Atlas region in southern Morocco and died there in the early 1950s. Impressed by his healing powers and shamanic virtuosity, Moroccan Jews are intrigued by his lifestyle and contacts with the Muslim and the demonic worlds that dangerously blurred his Jewish identity. Based on interviews with Moroccan Jews conducted in the late 1980s, Without Bounds proposes multiple readings of Wazana's life. Yoram Bilu re-creates the influences and important moments in Wazana's life and evaluates his character from psychological and anthropological perspectives. Human- and demon-bound, holy and impure, Jew and Muslim, old and young, Rabbi Ya'aqov Wazana dissolved the boundaries of the major social categories in Morocco and integrated them into his identity.
16. The Song of the Sirens: The Psychology of Wazana17. Without Bounds: Wazana the Symbolic Type; 18. Wazana of the Heart; Epilogue: Wazana's Afterlife; Notes; Bibliography; Index
16 black & white photographs.
The publication of this volume in a freely accessible digital format has been made possible by a major grant from the National Endowment for the Humanities and the Mellon Foundation through their Humanities Open Book Program.
Professional and scholarly.
Description based on print version record.
Keywords: Wazana, YŁacov; Rabbis; Medicine, Popular; Medicine, Magic, mystic, and spagiric; SOCIAL SCIENCE -- Folklore & Mythology; SOCIAL SCIENCE -- Jewish Studies; HISTORY -- Jewish; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; Medecine -- Ouvrages de vulgarisation; Medecine magique, mystique et spagirique -- Maroc; Rabbins -- Maroc -- Biographies; Medicine, Popular; Medicine, Magic, mystic, and spagiric -- Morocco; Rabbis -- Morocco -- Biography; Morocco; Biographies; Biographies; Biographies; Biography; Electronic books